2010
DOI: 10.1038/gt.2010.41
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ is essential for protection against nonalcoholic steatohepatitis

Abstract: Peroxisome proliferator-activated receptor-g (PPARg) is a transcription factor that regulates lipid metabolism and inflammatory responses. Certain PPARg ligands improve nonalcoholic steatohepatitis (NASH). The role of PPARg itself in NASH remains poorly understood. The functional consequences of PPARg in the development of steatohepatitis through gene deficiency or gene overexpression of PPARg delivered by adenovirus (Ad-PPARg) were examined. Our results show that PPARg-deficient (PPARg +/À ) mice fed the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 31 publications
3
54
1
1
Order By: Relevance
“…PPARα‐ as well as PPARγ‐deficient mice are more sensitive to the development of steatohepatitis under an MCD than wild‐type mice 21, 22. Using selective PPAR agonists, it was reported that Wy‐14,643 (a PPARα agonist), GW501516 (a PPARδ agonist), and PPARγ activation by pioglitazone prevent and/or reverse MCD‐induced steatohepatitis 21, 22, 23, 24, 25. In the foz/foz model, a protective effect on steatohepatitis was observed with PPARα agonist treatment 15…”
Section: Discussionmentioning
confidence: 99%
“…PPARα‐ as well as PPARγ‐deficient mice are more sensitive to the development of steatohepatitis under an MCD than wild‐type mice 21, 22. Using selective PPAR agonists, it was reported that Wy‐14,643 (a PPARα agonist), GW501516 (a PPARδ agonist), and PPARγ activation by pioglitazone prevent and/or reverse MCD‐induced steatohepatitis 21, 22, 23, 24, 25. In the foz/foz model, a protective effect on steatohepatitis was observed with PPARα agonist treatment 15…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the liver, luteolin treatment in the HFDfed mice elevated lipogenesis through increasing PPARg protein expression in adipose tissue. Wu et al (33) reported overexpression of PPARg delivered by adenovirusPPARg attenuated steatohepatitis by redistribution of FA from liver to adipose tissue by enhancing expression of FA uptake genes and lipogenic genes in adipose tissue. Luteolin significantly reduced the plasma FFA level with a simultaneous increase in adipocyte FA uptake gene (Cd36, Ffar3, Fabp4, and Lpl) expressions, leading to the reduction of hepatic lipotoxicity via the increased FFA flux to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…So far, activating agonists of PPARs such as Wy-14,643 and rosiglitazone have been tested for their effectiveness in diminishing the symptoms of NASH (12,39). However, the trials have not yet been successful, because the clinically applied PPAR agonists, rosiglitazone and pioglitazone, have several side effects such as edema, increased adiposity, liver toxicity, myocardial infarction, and heart failure (30,31).…”
Section: Fig 2 (Continued)mentioning
confidence: 99%